2017
DOI: 10.1016/j.ijnss.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical education and student satisfaction: An integrative literature review

Abstract: The clinical component of undergraduate clinical education is a critical area in nursing programs. Faculty shortages have made recruitment of clinical faculty and clinical teaching more challenging. As such, alternate models of clinical faculty assignments are being explored to address faculty shortages. This article contains an extensive literature review conducted to survey models of clinical education and student satisfaction with the clinical environment. The purpose of this paper is to examine student sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 23 publications
1
41
0
1
Order By: Relevance
“…6 Furthermore, they have identified the reasons for faculty shortage including lower compensation of faculty nurses compared to clinical nurses, less attractive position of faculty members, aging nursing faculty, and lack of facilities for nurses to obtain higher education. 6 Students in the current study have also reported that clinical teachers rarely visit them in clinical placement and too many students are supervised by a single clinical teacher as an alarming barrier. A study conducted in China demonstrated uncertainty among students in relation to what they could expect from the clinical teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Furthermore, they have identified the reasons for faculty shortage including lower compensation of faculty nurses compared to clinical nurses, less attractive position of faculty members, aging nursing faculty, and lack of facilities for nurses to obtain higher education. 6 Students in the current study have also reported that clinical teachers rarely visit them in clinical placement and too many students are supervised by a single clinical teacher as an alarming barrier. A study conducted in China demonstrated uncertainty among students in relation to what they could expect from the clinical teachers.…”
Section: Discussionmentioning
confidence: 99%
“…5 Therefore, clinical learning serves as an integral part of nursing curriculum in order to provide nursing students the opportunities to practice and become competent in the knowledge and skills which are important for professional practices. 6 Literature has identified a range of hindrances to clinical learning including anxiety of possible criticism from other students, committing mistakes, communication with health care team and patients, approach to critically ill patients, the inappropriate behavior of clinical staff nurses, 7 ward environment, the culture and complexities of care and the supervisory relationship between students, clinical and educational institutions. 8 Poor learning environment has adverse effects on the professional development process, and its dynamic nature could pose challenges to the students.…”
mentioning
confidence: 99%
“…CLUs were inspired by the DEU model and are self-directed clinical environments where students develop learning plans that identify their individual set rotations, their learning assignment, and the preceptor that they will work with. The student's learning plan is shared among the clinicians and therefore all on the unit are aware and involved in providing the learner with opportunities to build on their knowledge and practical experience (Callaghan et al, 2009;Phillips and Aktan, 2017). The results of the study conducted Callaghan et al (2017) were mixed in that nursing students found advantages and disadvantages in working with the CLU and traditional 1:1 preceptorship model.…”
Section: Collaborative Learning Units (Clu)mentioning
confidence: 99%
“…This study employed a new model developed by this research team, entitled Shared Clinical Teaching (SCT), which is defined as two faculty sharing responsibilities for a clinical group [15]. The purpose of this research study was to examine student satisfaction regarding the effectiveness of the SCT model.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this research study was to examine student satisfaction regarding the effectiveness of the SCT model. The premise of SCT is that a clinical group will be “shared” by two clinical faculty [15]. Two faculty with expertise in the clinical specialty are partnered for the duration of the rotation.…”
Section: Introductionmentioning
confidence: 99%